Immunization of Mice with a Live Transconjugant Shigella Hybrid Strain Induced Th1 and Th17 Cell‐Mediated Immune Responses and Confirmed Passive Protection Against Heterologous Shigellae. (February 2016) - Nag, D.; Koley, H.; Sinha, R.; Mukherjee, P.; Sarkar, C.; Withey, J. H.; Gachhui, R.
Abstract: An avirulent, live transconjugant Shigella hybrid (LTSHΔ stx ) strain was constructed in our earlier study by introducing a plasmid vector, pPR1347, into a Shiga toxin gene deleted Shigella dysenteriae 1. Three successive oral administrations of LTSHΔ stx to female adult mice produced comprehensive passive heterologous protection in their offspring against challenge with wild‐type shigellae. Production of NO and different cytokines such asIL‐12p70, IL‐1β and IL‐23 in peritoneal mice macrophages indicated that LTSHΔ stx induced innate and adaptive immunity in mice. Furthermore, production of IFN‐γ, IL‐10 and IL‐17 in LTSH‐primed splenic CD4+ T cell suggested that LTSHΔ stx may induce Th1 and Th17 cell‐mediated immune responses. Exponential increase of the serum IgG and IgA titre against whole shigellae was observed in immunized adult mice during and after the immunization with the highest peak on day 35. Antigen‐specific sIgA was also determined from intestinal lavage of immunized mice. The stomach extracts of neonates from immunized mice, mainly containing mother's milk, contained significant levels of anti‐LTSHΔ stx immunoglobulin. These studies suggest that the LTSHΔ stx could be a new live oral vaccine candidate against shigellosis in the near future.